Cycling performance after accumulated load: does durability change during a cycling season? - Voet, J.; Lamberts, R.; de Koning, J.; van Erp, T. (Journal of Science and Cycling, 2023)
Durability is the ability to produce high power outputs after accumulated load (at the end of a race), which has been shown to be an important success factor in professional road cycling (van Erp et al. 2020; Leo et al. 2021; Mateo-March et al. 2022; Muriel et al. 2022). Gross efficiency (GE), fat oxidation (FATox) and carbohydrate oxidation (CHOox) have been proposed as underlying physiological factors for durability, as changes have been shown to be related to a decrease in performance after accumulated load (Noordhof et al. 2020; Passfield & Doust, 2000; Stevenson et al. 2022), although there is much debate on this topic. Therefore, the aim of this study is to investigate durability and the underlying physiological factors in semi-professional cyclists. Secondly, this study investigates how durability and certain physiological factors changed during a cycling season.